2016
DOI: 10.1161/strokeaha.115.012091
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol, Ibuprofen, and Recurrent Major Cardiovascular and Major Bleeding Events in 19 120 Patients With Recent Ischemic Stroke

Abstract: T he association between nonsteroidal anti-inflammatory drugs (NSAIDs) and cardiovascular risk is well established, particularly in high-risk populations.1 Paracetamol (acetaminofen) is the most widely used analgesic and antipyretic worldwide.2 It is commonly accepted that it has a better safety profile than NSAIDs, and thus it is usually the treatment of choice in many medical conditions. In patients with a high cardiovascular risk, recommendations state that paracetamol should be chosen over NSAIDs.3 Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Patients with large, severe ischemic stroke with residual handicap measured by a modified Rankin score >3, who are more prone to bleed than those with minor ischemic stroke, were also excluded in both trials. Interaction with other drugs prescribed during the course of the trial may also be an important bleeding factor, such as paracetamol or ibuprofen prescriptions [27]. We found that these drugs were associated with almost a doubling in major hemorrhages [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with large, severe ischemic stroke with residual handicap measured by a modified Rankin score >3, who are more prone to bleed than those with minor ischemic stroke, were also excluded in both trials. Interaction with other drugs prescribed during the course of the trial may also be an important bleeding factor, such as paracetamol or ibuprofen prescriptions [27]. We found that these drugs were associated with almost a doubling in major hemorrhages [27].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction with other drugs prescribed during the course of the trial may also be an important bleeding factor, such as paracetamol or ibuprofen prescriptions [27]. We found that these drugs were associated with almost a doubling in major hemorrhages [27]. It is thus reasonable to think, but yet to be validated, that in the Intracranial-B 2 LEED 3 S score addition of paracetamol or ibuprofen can be substituted by the ‘dual antiplatelet therapy' variable.…”
Section: Discussionmentioning
confidence: 99%
“…and they found increased relative rate of mortality from 0.95 to 1.63 and for cardiovascular adverse events risk ratio of all events increased from 1.19 to 1.68 and also that gastrointestinal adverse events or bleeds were found to increase from 1.11 to 1.49; moreover, kidney damage odds ratio increased more than 30% [23]. Another notable paper published on acetaminophen's cardiovascular side effect could only demonstrate small association with major cardiovascular events and short-term use of acetaminophen (odds ratio 1.21, 95% confidence interval 1.04-1.42) [24].…”
Section: Acetaminophenmentioning
confidence: 97%
“…Acetaminophen causes major bleeding events at therapeutically relevant doses in patients with recent ischemic stroke [13]. Possible mechanisms could involve the participation of acetaminophen metabolites such as NAPQI [10] or cis-EpOA, rather than thromboxane A2 inhibition in platelets by acetaminophen [7].…”
Section: Rosmentioning
confidence: 99%